2014
DOI: 10.1182/blood.v124.21.3643.3643
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD30, Resistance to MMAE, and Upregulation of MDR1 Are All Associated with Resistance to Brentuximab Vedotin

Abstract: Background: Both Hodgkin lymphoma (HL) and anaplastic large cell lymphoma (ALCL) express surface CD30. Brentuximab vedotin (BV) is an antibody-drug conjugate that delivers a potent cytotoxic agent, monomethyl auristatin E (MMAE), specifically to cells expressing surface CD30. Although BV elicits a high response rate (75% in HL and 86% in ALCL), the majority of patients who do not attain complete response (CR) will eventually develop resistance to BV. It is not known whether resistance to BV is through a) CD 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, this delivery system is plagued by cellular mechanisms that reduce intracellular drug levels and ultimately results in resistance. 7,8 For example, lymphoma cells resistant to brentuximab vedotin were able to down regulate CD30 expression and increase the expression of MDR 1. Breast cancer cells resistant to trastuzumab emtansine also down regulated Her2 expression and increased expression of MDR pumps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this delivery system is plagued by cellular mechanisms that reduce intracellular drug levels and ultimately results in resistance. 7,8 For example, lymphoma cells resistant to brentuximab vedotin were able to down regulate CD30 expression and increase the expression of MDR 1. Breast cancer cells resistant to trastuzumab emtansine also down regulated Her2 expression and increased expression of MDR pumps.…”
Section: Discussionmentioning
confidence: 99%
“…This recirculation of bile acids is also a likely contributing aspect for the improved tumor targeting by 64 Cu-A14-ChAcNLS. For applications toward targeted chemotherapy, because these drugs transported by current ACs are readily exported outside of the cell, 7,8 this new advancement in AC technology will most likely have an impact in the retention of chemotherapeutics due to the fact that the drug remains attached to the AC and are sheltered away from lysosome proteases and subsequent exportation. Further testing will have to be conducted to see if this strategy has a therapeutic advantage over the current system of intracellular drug accumulation by ACs.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common ways of cells to become resistant to an antibody-based therapy is the loss of antigen expression, or epitope modification, to prevent antibody binding and internalisation or signaling [6]. This mechanism has not only been seen with naked antibody therapy, but also with ADCs in vitro and clinically [7][8][9]. Our study showed that the binding and subsequent internalisation of the CD25 and HER2 antibodies was not affected in the acquired resistant cell lines and the apparent affinity of the antibody to all the cell lines was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Both pre-clinical and clinical studies have been carried out on currently approved ADCs and the mechanism of acquired resistance generally falls into two major categories; related to the antibody portion of the ADC, or related to the drug/drug-linker portion of the ADC [5]. Tumor cells that have become refractory to monoclonal antibody (mAb) therapy often show downregulation of the target antigen or impaired mAb-antigen complex internalisation [6], a resistance mechanism that has also been reported with trastuzumab emtansine (T-DM1) [7,8], brentuximab vedotin (BV) [9] and gemtuzumab ozogamicin (GO) [10].…”
Section: Introductionmentioning
confidence: 99%